Adding heat stress to repeated-sprint training in hypoxia does not enhance performance improvements in canoe/kayak athletes - Yamaguchi, K.; Kayanuma, S.; Imai, A.; Hayashi, N.; Makino, A.; Goto, K. (European Journal of Applied Physiology, 2022)
Purpose: The present study investigated the effects of adding heat stress to repeated-sprint training in hypoxia on performance and physiological adaptations in well-trained athletes. Methods: Sixteen canoe/kayak sprinters conducted 2 weeks of repeated-sprint training consisting of three sets of 5 × 10 s sprints with 20 s active recovery periods under conditions of either normobaric hypoxia (RSH, FiO2: 14.5%, ambient temperature: 18 °C, n = 8) or combined heat and normobaric hypoxia (RSHH, FiO2: 14.5%, ambient temperature: 38 °C, n = 8). Before and after training, the 10 × 10 s repeated-sprint ability (RSA) test and 500 m time trial were performed on a canoe/kayak ergometer. Results: Peak and average power outputs during the RSA test were significantly improved after training in both RSH (peak power: + 21.5 ± 4.6%, P < 0.001; average power: + 12.5 ± 1.9%, P < 0.001) and RSHH groups (peak power: + 18.8 ± 6.6%, P = 0.005; average power: + 10.9 ± 6.8%, P = 0.030). Indirect variables of skeletal muscle oxygen extraction (deoxygenated hemoglobin) and blood perfusion (total hemoglobin) during the RSA test were significantly increased after training in the RSH group (P = 0.041 and P = 0.034, respectively) but not in the RSHH group. In addition, finish time during the 500 m time trial was significantly shortened after the training only in the RSH group (RSH: - 3.9 ± 0.8%, P = 0.005; RSHH: - 3.1 ± 1.4%, P = 0.078). Conclusion: Adding heat stress to RSH does not enhance performance improvement and may partially mask muscle tissue adaptation.